Resection and Abdominal Wall Reconstruction of a Desmoid Tumor with Endometrioma Features - Jaqueline Majors; Nathaniel F. Stoikes; Reza Nejati; Jeremiah L. Deneve (Case Reports in Surgery)
Desmoid tumors are rare, musculoaponeurotic mesenchymal origin tumors arising from the proliferation of well-differentiated fibroblasts. Desmoid tumors may arise from any location with the abdominal cavity, abdominal wall and extremity locations being most frequent. We present the case of a 35-year-old female with a history of endometriosis who presented palpable abdominal mass and cyclic abdominal pain. Resection was performed for a presumed desmoid soft tissue tumor. Final pathology demonstrated desmoid histology admixed with abdominal wall endometriosis (endometrioma). This unique pathologic finding has only been rarely reported and is discussed with a brief review of the literature.